2013
DOI: 10.1002/jgrd.50762
|View full text |Cite
|
Sign up to set email alerts
|

The impact of abrupt suspension of solar radiation management (termination effect) in experiment G2 of the Geoengineering Model Intercomparison Project (GeoMIP)

Abstract: [1] We have examined changes in climate which result from the sudden termination of geoengineering after 50 years of offsetting a 1% per annum increase in CO 2 concentrations by a reduction of solar radiation, as simulated by 11 different climate models in experiment G2 of the Geoengineering Model Intercomparison Project. The models agree on a rapid increase in global-mean temperature following termination accompanied by increases in global-mean precipitation rate and decreases in sea-ice cover. There is no ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
155
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 149 publications
(169 citation statements)
references
References 35 publications
12
155
2
Order By: Relevance
“…Both experiments run geoengineering for 50 y starting in 2020. Following cessation of geoengineering in 2069, the scenarios run for a further 20 y to provide information on the so-called "termination effect" (40). We analyzed three models that have completed the G3 experiment and seven models simulating G4; eight models have run at least one of them, and 10 simulations were done in total.…”
Section: Methodsmentioning
confidence: 99%
“…Both experiments run geoengineering for 50 y starting in 2020. Following cessation of geoengineering in 2069, the scenarios run for a further 20 y to provide information on the so-called "termination effect" (40). We analyzed three models that have completed the G3 experiment and seven models simulating G4; eight models have run at least one of them, and 10 simulations were done in total.…”
Section: Methodsmentioning
confidence: 99%
“…Most previous studies comparing solar dimming and stratospheric aerosol SRM have concentrated on the climate mean response (Jones et 25 al., 2011;Niemeier et al, 2013;Ferraro et al, 2014). Curry et al (2014) examined the effect of G1 geoengineering on the same metrics of extreme temperature and precipitation response (both magnitude Atmos.…”
Section: Discussionmentioning
confidence: 99%
“…Tilmes et al (2013) observed, using a 25 larger ensemble of models, that G1-abrupt4×CO2 results in a robust decrease in monsoonal precipitation, while it increases under abrupt4×CO2. However, the change under G4-rcp45 is not as robust, at least partially due to the lowered mean temperature changes and land-sea thermal contrast response to the stratospheric aerosol injection.…”
Section: Spatial Response In Extremesmentioning
confidence: 93%
“…5 Some authors 5 distinguish between technical and social lock-in: technical lock-in being used to refer to the kinds of commitments that would accompany particular technological approaches such as SAI due to the existence of the so-called 'termination effect'. The term is used to refer to the fact that if a programme of Stratospheric Aerosol Injection were implemented but then discontinued, there would be a rapid spike in global temperature that would likely be more damaging than the more gradual temperature increases that would have taken place in the absence of such an intervention, 6 hence societies would be 'locked-in' to continuing the activity. Social lock-in, in this case, is used to refer to the ways in which many of the proposed technologies [e.g., direct air capture (DAC)], would be dependent on the existence of a highly capital-intensive physical infrastructure, the large sunk costs in which would create vested interests in keeping facilities operational, and hence would lead to various types of inertia and lock-in.…”
Section: Socio-technical Lock-in and Climate Geoengineeringmentioning
confidence: 99%